Should I stay or should I go? Behavioral adjustments of fur seals related to foraging success. (13th April 2022) - Chevallay, Mathilde; Guinet, Christophe; Jeanniard-Du-Dot, Tiphaine
Abstract: Understanding foraging strategies and decision-making processes of predators provide crucial insights into how they might respond to changes in prey availability and in their environment to maximize their net energy input. In this work, foraging strategies of Antarctic fur seals ( Arctocephalus gazella, AFS) and Northern fur seals ( Callorhinus ursinus, NFS) were studied to determine how they adjust their foraging behavior according to their past prey capture experiences. AFS on Kerguelen Islands are exclusively oceanic divers, while NFS population of St Paul Island shows both oceanic and neritic divers. We thus hypothesized that the two species would respond differently to a change in prey capture success depending on their foraging strategy. To test this, 40 females were equipped with tags that measured tri-axial acceleration, dive depth, and GPS coordinates, from which we derived prey capture attempts and behavioral metrics. Influence of prey capture success on horizontal and vertical movements of seals was investigated at different time scales: multi-dive, night, and trip. Both AFS and NFS traveled further during the day if they encountered low prey capture periods during the previous night. However, at the multi-dive scale, neritic NFS differed from oceanic NFS and AFS in terms of decision-making processes, e.g., both AFS and oceanic NFS dived deeper in response to low prey capture rate periods, while neritic NFS did not. Similarities in decision-making processes between NFS and AFS foraging on pelagic prey suggest that pelagic vs. neritic prey type is a key factor in defining foraging decisions of diving marine predators. Abstract : Decisions predators make while foraging affect their feeding efficiency, which also affects these decisions in return. To better understand these intricate relationships, we studied the impacts of feeding success on foraging behaviors of two species of fur seals. Seals responded to a decrease in capture success by adjusting both their movement and diving patterns, although in different ways depending on their habitat and targeted prey. Our study provides insight into seals might respond to changes in prey availability.